Soft-sediment deformation structures in the Mio-Pliocene Misaki Formation within alternating deep-sea clays and volcanic ashes (Miura Peninsula, Japan) - Mazumder, Rajat; van Loon, A.; Malviya, V.; Arima, M.; Ogawa, Y. (Elsevier Science BV, 2016)
The Mio-Pliocene Misaki Formation of the Miura Group (Miura Peninsula, Japan) shows an extremely wide variety of soft-sediment deformation structures. The most common deformation structures are load casts and associated flame structures, dish-and-pillar structures, synsedimentary faults, multilobated convolutions, chaotic deformation structures, sedimentary veins and dykes, and large-scale slides and slump scars. The formation, which accumulated in a deep-sea environment (2000–3000 m), is well exposed in and around Jogashima; it consists of relative thin (commonly dm-scale) alternations of deep-marine fine-grained sediments and volcanic ejecta that are, as a rule, coarse-grained. Since the formation represents fore-arc deposits of the Izu-Bonin and the Honsu arc collision zone, it might be expected that tectonic activity also played a role as a trigger of the soft-sediment deformation structures that abound in these sediments. This is indicated, indeed, by the abundance of soft-sediment deformations over large lateral distances that occur in numerous beds that are sandwiched between undeformed beds. On the basis of their characteristics and the geological context, these layers can be explained satisfactorily only by assuming deformation triggered by seismicity, which must be related to the Izu-Bonin and Honsu arc collision. The layers thus form deep-marine seismites.